PERAN LEMBAGA ISLAM DALAM MENGENTASKAN KEMISKNAN (Studi Kasus Pada Baitul Maal Hidayatullah Cabang Malang) - Fajri Mas Afifah; Arif Hoetoro (Jurnal Ilmiah Mahasiswa FEB, 2014)
Poverty is a condition in which an individual can’t fill their basic needs. Islam considers that poverty is a problem that must be resolved quickly. Islam has solutions to reduce poverty by working  or  an  individual  obligation  for  themselves  and  Zakah,  Infaq,  Sedekah,  and  Waqf (ZISWAF) or an individual obligation foranother person. ZISWAF is an Islamic income redistribution. Islam has an institution that collecting, utilizing, and distributing ZISWAF namely Baitul Maal. Baitul Maal Hidayatullah choose to distribute their funds through four main programs, they are: religious proselytizing, education, economic, and social humanity. BMH also has a different distribution system, they distribute their fund through the third party namely da’i or coordinator, aplicating this system expected that the given fund can be allocated as a given function.   Keyword: Poverty, ZISWAF, Baitul Maal